Labor-market attachment and training participation - Toshie Ikenaga; Daiji Kawaguchi (Institute for the Study of Labor (IZA), 2010)
This paper examines how expected attachment to the labor market and expected tenure at a specific firm affect training participation. The results, based on cross-sectional data from Japan, indicate that expected attachment to the labor market affects participation in both employer- and worker-initiated training, while expected tenure at a specific firm mainly explains participation in employer-initiated training. These two attachment indices explain almost half of the gender gap in training participation. Employers in a less competitive labor market are more likely to offer employer-initiated training to their workers.
Keywords: J16; J24; J61; J63; 330; training; labor market attachment; job tenure; gender; Japan